Religious Tourism Development Strategy in Improving Community Economy at Mount Santri, Bojonegara District, Serang Regency, Banten - Dian Sudiantini; Bintang Narpati (PT FORMOSA CENDEKIA GLOBAL, 2022)
Religious tourism is an activity that is often carried out by most Muslims around the world, including in Indonesia. Pandeglang is part of the province of Banten, where in this area we find many religious tourist attractions, one of which is the religious tourist site of Mount Santri which is located in the Bojonegara District, Serang Regency, Banten, where this place is visited by many pilgrims, both from pilgrims from Serang, as well as from outside Serang. Serang is one of the districts part of Banten province, where in the Serang Banten area there are many religious tourist attractions including the Sultanate of Banten, Syeh Nawawi Tanahara, Sultan Agung Tirtayasa, Gunung Santri and so on. One of the interesting religious tourism places is Mount Santri which is located in the District of Bojonegara, Serang Regency, this research uses qualitative research.